The ARIC-PET amyloid imaging study: Brain amyloid differences by age, race, sex, and APOE. (2nd August 2016) - Gottesman, Rebecca F.; Schneider, Andrea L.C.; Zhou, Yun; Chen, Xueqi; Green, Edward; Gupta, Naresh; Knopman, David S.; Mintz, Akiva; Rahmim, Arman; Sharrett, A. Richey; Wagenknecht, Lynne E.; Wong, Dean F.; et al.
Abstract : Objective: To evaluate differences in amyloid deposition in a community-based cohort without dementia by age, sex, race, education, and APOE ε4 allele status. Methods: Recruited from the longitudinal Atherosclerosis Risk in Communities study, 329 participants without dementia, ages 67–88 years, were imaged using florbetapir PET at 3 US community sites (Washington County, Maryland; Forsyth County, North Carolina; and Jackson, Mississippi). Standardized uptake value ratios (SUVRs) were calculated; global cortical SUVR >1.2 was evaluated as the primary outcome. Age, race, sex, education level, and number of APOE ε4 alleles were evaluated in multivariable models including vascular risk factors, brain white matter hyperintensity and total intracranial volume, and cognitive status. Results: A total of 141 of the participants (43%) were black. In multivariable models, odds of elevated SUVR was increased in participants with increasing age (odds ratio [OR] 1.63, 95% confidence interval [CI] 1.01–2.65 per 10 years of age) and black race (OR 2.08, 95% CI 1.23–3.51) but did not differ by educational level. Each ε4 allele was associated with increased odds of elevated SUVR (OR 2.65, 95% CI 1.61–4.39). Conclusions: In this community-based cohort without dementia, florbetapir uptake is associated with older age and APOE genotype. Black race was associated with higher SUVR, after adjusting for demographics, vascular risk factors, cognitive status, white matter hyperintensity volume, and APOE genotype, with effect sizes nearing those seen for APOE ε4. Replication of these findings is needed in other cohorts, and reasons for and consequences of these observed differences by race warrant further study.